MEMPERKUAT LITERASI ANAK USIA DINI DI MASA PANDEMI - Muflih Ma'mun; Ai Halida (Jurnal Al Maesarah, 2022)
The Covid-19 pandemic changed the educational paradigm that has been focused on the learning process in schools into a shared responsibility between schools and parents. Parents during pandemics have the same responsibility in educating and accompanying their children to study at home, and this becomes a problem for parents because of the lack of ability to teach children. In early childhood this condition is so pronounced, especially in a number of parents in Bunijaya Village, Gununghalu Subdistrict who generally do not understand how to teach children while at home, so this needs special assistance. Through strengthening early childhood literacy, in addition to improving children's literacy, it can also provide education for parents about learning mentoring patterns, especially in Caslitung and BTQ (Read the Quran )in early childhood in Bunijaya Village, Gununghalu District.